Avaliação de enterobactérias resistentes aos carbapenêmicos isoladas em um hospital terciário - Silva, Danielly da Costa (2017)
Resistance to antimicrobials in enterobacteria is a serious public health problem. The rapid spread of genes and antimicrobial resistance mechanisms limit the therapeutic options and imply an increase in the morbimortality rate of patients. Carbapenemase-producing bacteria such as Klebsiella pneumoniae are considered important agents of hospital infections due to the production of carbapenemases. The objective of this study was to evaluate 178 samples of carbapenem-resistant Enterobacteriaceae (CREs) by phenotypic methods of disc diffusion and Blue Carba, their antimicrobial susceptibility profile by automated system VITEK®2 (bioMérieux), and to detect by Polymerase chain reaction (PCR) the blaKPC type carbapenemase encoding gene. These isolates come from a University Hospital in Santa Maria (HUSM), Santa Maria/RS, and were collected in a period of one year (July 2014 to July 2015). Isolates were assessed using disk diffusion tests with β-lactamases inhibitors such as phenylboronic acid (AFB), cloxacillin (CLOXA), and ethylenediaminetetraacetic acid (EDTA). Isolates with differences in zone diameters ≥ 5mmfor disks supplemented or not were considered producers of carbapenemases. K. pneumoniae was the most prevalent CRE, which appeared in 80.3% cases (n=143). Among clinical materials the rectal swab was responsible for 43.4% of the isolations (n = 62). Among the CREs identified in this study the growth of 56.7% (n = 101) isolates which were putative producers of K. pneumoniae carbapenemase (KPC) were inhibited by AFB, whereas 7.3% (n = 13) isolates were inhibited by both AFB and CLOXA and were considered as putative producers of plasmid-mediated AmpC; approximately 3.4% (n = 6) were inhibited by EDTA, which possibly produced metallo-β-lactamase. Lastly, 32.6% (n = 58) cases showed negative results for AFB, CLOXA, and EDTA sensitivity, and represented another class of β-lactamases and/or mechanism of resistance. For genotypic detection, 172 samples of CRE from different clinical specimens were obtained. K. pneumoniae was a prevalent microorganism with 139 (80.81%) of the isolates. The most isolated clinical material was rectal swab (surveillance culture) with 48 samples (34.53%). The blaKPC gene was detected in 124 (72.09%) isolates. In the disk diffusion technique by AFB 111 (64.53%) were KPC and by Blue-Carba 121 (70.34%). Considering PCR as the gold standard for this mechanism of resistance, AFB showed 80% sensitivity and 75% specificity. The Blue-Carba biochemical test showed 90% sensitivity and 81% specificity. Resistance to colistin was identified in 25 isolates of carbapenem resistant Klebsiella pneumoniae (CR-Kp), and 10 (7.19%) patients died of CR-Kp and three (2.16%) of CR-Kp and resistant to colistin (CPR-Kp). The identification of these multiresistant bacteria by the laboratory is of paramount importance for the immediate patient isolation, besides the adoption of rigorous measures of prevention and control of infections for these multiresistant microorganisms.